PENGARUH MANAJEMEN MODAL KERJA TERHADAP RENTABILITAS PERUSAHAAN PADA PT SEPATU BATA, TBK - Chaidir Chaidir; Shanti Lintang Kawuryan (Universitas Pakuan, 2015)
Generally, the company's goal is to obtain the optimal profit, maintaining the company's survival anddevelopment. Thus, companies must consider the profitability of the company. Profitability of PT. ShoesBata Tbk influenced by various factors of financial factors that can be measured using financial ratios.Based on the statistical results of the coefficient of correlation coefficient between the working capitalturnover and return on investment of -0.135. Indicates that the value obtained is very low correlationbelong to the weak negative correlation. The statistical results showed that the management of workingcapital to profitability (ROI) has a negative relationship and the direction does not significantly influencethe profitability (ROI).